Effect of Bleaching on Hardness, Gloss, and Color Change of Weathered Woods - Budakçı, Mehmet; Karamanoğlu, Mehmet (BioResources, 2014)
The aim of this study was to eliminate the problems of hardness, gloss, and color change of some wood materials exposed to weathering conditions using a bleaching procedure to attempt to return the wood material to its natural state. For this, wood samples of Scots pine (Pinus sylvestris L.), Eastern beech (Fagus orientalis L.), sessile oak (Quercus petraea L.), and chestnut (Castanea sativa Mill.) were exposed to weathering conditions based on 12 months ASTM D-1641, followed by a bleaching procedure using 18% solutions of S1 (NaOH + H2O2), S2 (NaOH + Ca(OH)2), S3 (KMnO4 + NaHSO3 + H2O2), S4 (NaSiO3 + H2O2), and the commercial product S5 (Cuprinol Decking Restorer- (H2C2O4 + C2H4(OH)2). The color, gloss, and hardness changes of samples were determined according to ASTM D 2244-2, EN ISO 2813, and ASTM D 2240 standards. As a result, hardness and gloss values of all woods decreased due to weathering conditions and the wood color turned grey due to degradation. When comparing the weathered samples to the bleached samples, the hardness value was found to be highest in pine wood bleached with the S2 solution, and the gloss value was highest in oak wood bleached with the S1 solution. The greatest color change was found in pine, beech, and chestnut samples bleached with the S4 solution and in oak samples bleached with the S1 solution.
Keywords: Weathering conditions; Bleaching procedure; Hardness; Wood material; Gloss; Color; TP248.13-248.65; Biotechnology; 15. Life on land